Extracellular succinate derived from ectopic milieu drives adhesion and implantation growth of ectopic endometrial stromal cells via the SUCNR1 signal in endometriosis - Qi Tian; Jingyao Ruan; Yuning Wang; Yinping Xiao; Qi Cheng; Yun Chen; Mingqing Li; Kaikai Chang; Xiaofang Yi (Cell Communication and Signaling, 2024)
Abstract Background As a dual-function metabolite, succinate has emerged in cell function and plays a key signaling role in linking mitochondrial function to other cellular functions. Succinate accumulation in the cytoplasm is commonly associated with hypoxia in the microenvironment and immune cell activation. Extracellular succinate released into the microenvironment is considered an inflammatory alarm that can be sensed by its membrane receptor SUCNR1, which boosts proinflammatory responses and acts akin to classical hormones and cytokines. Succinate plays an important role in the development of inflammatory diseases. Whether succinate facilitates the progression of endometriosis (EMs), characterized by chronic inflammation and peritoneal adhesion, is worth exploring. Objective We mimicked the ectopic milieu in vitro and in vivo to evaluate the main source and potential role of succinate in endometriosis. We assessed the molecular and functional effects of succinate on macrophages and peritoneal mesothelial cells in peritoneal cavity. The effect of succinate/SUCNR1 signaling on ectopic endometrial stromal cells (ESCs) was further explored in this study. Methods In this study, we used targeted organic acid metabolomics analysis and in vitro assays to assess the potential accumulation of succinate in the peritoneal fluid of EMs patients. We examined its correlation with disease severity, Visual Analogue Scale, and the Endometriosis Fertility Index. Flow cytometry, enzyme linked immunosorbent assay, western blot assay, quantitative real-time PCR, and other molecular biology techniques were used to explore the potential mechanisms. Results By mimicking the ectopic milieu, we constructed an in vitro co-culture system and found that M1 polarized macrophages and that the peritoneal mesothelial cell line (HMrSV5) mainly released succinate into their microenvironment and activated the succinate receptor (SUCNR1) signal, which further polarized the macrophages and significantly enhanced the invasive survival of ESCs, and the adhesion to the peritoneum. We further investigated the pathological effects of extracellular succinate in vivo using a xenograft mouse models of endometriosis. Conclusions Succinate-SUCNR1 signaling facilitates the creation of inflammatory cells and plays a vital role in EMs progression and peritoneal adhesion. Our work on the molecular mechanisms underlying succinate accumulation and function will help elucidate the phenotypic mysteries of pain and infertility in EMs. Video Abstract